Gemcitabine and docetaxel in relapsed and unresectable high-grade osteosarcoma and spindle cell sarcoma of bone. Issue 1 (December 2016) - Palmerini, E.; Jones, R.; Marchesi, E.; Paioli, A.; Cesari, M.; Longhi, A.; Meazza, C.; Coccoli, L.; Fagioli, F.; Asaftei, S.; Grignani, G.; Tamburini, A.; et al.
Abstract Background Few new compounds are available for relapsed osteosarcoma. We retrospectively evaluated the activity of gemcitabine (G) plus docetaxel (D) in patients with relapsed high-grade osteosarcoma and high-grade spindle cell sarcoma of bone (HGS). Methods Patients receiving G 900 mg/m2 d 1, 8; D 75 mg/m2 d 8, every 21 days were eligible. Primary end-point: progression-free survival (PFS) at 4 months; secondary end-point: overall survival (OS) and response rate. Results Fifty-one patients were included, with a median age of 17 years (8–71), 26 (51 %) were pediatric patients. GD line of treatment: 2nd in 14 patients, ≥3rd in 37. 25 (49 %) patients had metastases limited to lungs, 26 (51 %) multiple sites. Histology: 40 (78 %) osteosarcoma, 11 (22 %) HGS. Eight (16 %) patients achieved surgical complete response (sCR2) after GD. Four-month PFS rate was 46 %, and significantly better for patients with ECOG 0 (ECOG 0: 54 % vs ECOG 1: 43 % vs ECOG 2: 0 %;p  = 0.003), for patients undergoing metastasectomy after GD (sCR2 75 % vs no-sCR2 40 %, p  = 0.02) and for osteosarcoma (osteosarcoma 56 % vs HGS 18 %;p  = 0.05), with no differences according to age, line of treatment, and pattern of metastases. Forty-six cases had RECIST measurable disease: 6 (13 %) patients had a partial response (PR), 20 (43 %) had stable disease (SD) and 20 (43 %) had progressive disease (PD). The 1-year OS was 30 %: 67 % for PR, 54 % for SD and 20 % for PD (p  = 0.005). Conclusions GD is an active treatment for relapsed high-grade osteosarcoma, especially for ECOG 0 patients, and should be included in the therapeutic armamentarium of metastatic osteosarcoma.